PROFESIONALISME WARTAWAN GORIAU.COM DALAM PELIPUTAN BERITA MEDIA ONLINE - Puri Retno Mutia; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Goriau.Com is one of the online media with the highest rating version alexa.com and also the fastest media in giving information. In the process of seeking information, GoRiau.com’s journalists are required to be able covering, searching and processing the news coverage their duties. But here researchers find the practice of news plagiarism on Goriau.com. This study aims to find out how the Professionalism of GoRiau.com’sJournalist in covering the online media news and to understand the obstacle for the journalists in covering the online media News.This study used descriptive qualitative method, conducted in GoRiau.com online media, Jalan Surya KartamaAgung 4A Pekanbaru. Determining the subjects conducted through purposive sampling techniques the number of subjects in this study as many 9 (nine) people, consisting of editor-in-chief GoRiau.com, four journalists GoRiau.com, chairman of unity journalists Indonesia (PWI) pekanbaru city, senior journalists reporter Indonesia (PWI) and two readers. Data analysis model miles and hubarman. Data collection technique is done by observation, interview and documentation. The theory used is social responsibility and the concept of journalistic code of ethics article 2.In thid research, found 2 (two) research result. The first not all journalists of GoRiau.com are professional in the covering of online media news. Second, some obstacles occur in the coverage causing journalists to be unprofessional in performing their duties. This happened to some GoRiau.com’s journalists who were in the local area. The quality of journalists' ability, personality and integrity of journalists as well as the limited number of journalists became an obstacle which caused some local journalists become an obstacly in it self that causes unprofessional in carrying out its duties.Keywoard: Professionalism, Journalist, Covering, Online Media